Efficacy of flaxseed in reducing blood pressure among patients with cardiovascular risk factors: A systematic review and meta-analysis of parallel randomized controlled trials - Refli Hasan; Raed Obaid Saleh; Rana H. Raheema; Hanen Mahmod Hulail; Irfan Ahmad; Deepak Nathiya; Parjinder Kaur (Journal of Cardiovascular and Thoracic Research)
The prevalence rate of hypertension is on the rise at an alarming rate. Studies conducted on the influence of flaxseed on blood pressure (BP) have come up with conflicting conclusions. The current investigation’s major purpose is to conduct a literature review and a meta-analysis focusing on the effect of flaxseed supplementation on BP in people with cardiovascular disease (CVD) risk factors. PubMed, Scopus, Web of Science, and Cochrane Central Library databases were searched from the inception date to April 2024 to find the randomized controlled trials (RCTs). A random-effects model combined the weighted mean difference (WMD). Standard methodologies were applied to evaluate publication bias, heterogeneity, and sensitivity analysis. Eighteen RCTs were included in the present systematic review and meta-analysis. Pooled analysis suggested that flaxseed supplementation can reduce systolic BP (SBP) (WMD: -4.75 mmHg, 95% CI: -7.05 to -2.44, P≤0.001; I2=93.6%) and diastolic BP (DBP) (WMD: -3.09 mmHg, 95% CI: -4.37 to -1.81, P≤0.001; I2=91.2%). In conclusion, the current meta-analysis has demonstrated that flaxseed supplementation can markedly lower BP in individuals exhibiting CVD risk factors. Given the significant heterogeneity, it is crucial to interpret the current results with careful consideration. In addition, further high-quality RCTs are required to better assess the causal relationships.